Exploration of motif patterns using the space-time-plane system and flat design stylization with La Galigo epic inspiration - Aghnia Fauzul Muslikhani; Morinta Rosandini; Gina Shobiro Takao (Gelar : Jurnal Seni Budaya, 2023)
The development of storytelling motifs is enhanced through the Space-Time-Plane (STP) system, a drawing technique that integrates Image Way and Grammar principles. This system adeptly represents spatial and temporal dimensions, facilitating the creation of illustrative storytelling. Its application extends to translating images into meaning and vice versa, showcasing its impact on the textile sector. Notably, it drives the evolution of non-repetitive motif compositions embodying story concepts presented with flat design styling. Despite its successes, applying the STP system to motif development poses challenges, particularly when incorporating motifs into product patterns, leading to story truncation. Conversely, the non-repetitive motif composition using the STP system ensures the entire narrative is encapsulated in a single image, preventing any intersection of motifs. Motif development with the STP system draws inspiration mainly from modern sources despite its closer connection to traditional Indonesian art, particularly heroic stories like the epic La Galigo. While developments inspired by heroic narratives, including La Galigo, exist, their visualization remains confined to single-image models. The primary aim of this research is to generate an inspirational motif rooted in Indonesian traditional art, specifically the La Galigo epic. This is achieved through the utilization of the STP system, flat design styling, and repetitive composition or repeated illustration models. Employing an exploratory method, the research culminates in a repetitive motif composition, providing an alternative resolution to the issue of truncated motifs in non-repetitive composition models. The study aspires to contribute significantly to research focused on enriching the application of the STP system in visualizing stories through the manipulation of textile motif compositions.